Strengthening Family Resilience Through a Spirituality-Based Approach: A Study of Mosque-Based Family Corner Programs in Malang City - Tri Leli Rahmawati; Mufidah Cholil; Mustafa Lutfi (Journal of Social and Humanities, 2026)
This study aims to analyze the role of spirituality in enhancing family resilience through mosque-based Family Corner programs in Malang City and to formulate a family resilience strengthening model based on Froma Walsh’s family resilience theory. This research employed a qualitative approach with a field research design. Data were collected through interviews, observations, and documentation in six mosques implementing Family Corner programs in Malang City and were analyzed using data reduction, data display, and conclusion-drawing techniques, supported by source and method triangulation. The findings reveal that Family Corner functions as a medium for strengthening family resilience through the development of religious coping and spiritual well-being, which reinforce family belief systems, organizational patterns, and communication processes. However, the implementation of the program continues to face several challenges, including limited human resources, insufficient operational support, low community participation, and underdeveloped digital services. Based on these findings, this study reformulates the Family Corner model through the lens of Froma Walsh’s theory by proposing three main strategies: spiritual anchoring to strengthen family belief systems, a mosque support system to reinforce family organization, and sacred dialogue to foster adaptive family communication. This model is supported by multidisciplinary counseling services, conducive service spaces, and promotive, preventive, and curative interventions grounded in spirituality. The study affirms that spirituality functions not only as a source of family resilience but also as a form of social capital capable of enhancing the adaptive capacity of Muslim families in confronting various contemporary crises.